Deep learning applications and intelligent decision making in engineering - Senthilnathan, Karthikrajan, 1991-; Shanmugam, Balamurugan, 1985-; Goyal, Dinesh, 1976-; Annapoorani, Iyswarya, 1976-; Samikannu, Ravi, 1982- (Advances in computational intelligence and robotics (ACIR) book series., 2021)
"This book explores the application of deep learning in building a smart world, ranging from smart cities, smart agriculture to smart homes"--